Evaluation of Blasting Geometry and Flyrock to Determine Safe Distance in Overburden Stripping Activities - Permana, Irfan Satria; Setiawan, M. Wahyudha; Oswara, Randy M. (Civiliza Publishing, Indonesia., 2025)
Blasting activities in open-pit mining are the main method for breaking up hard rocks, but they also have significant potential hazards, one of which is Flyrock. This study evaluates the blasting geometry towards Flyrock to determine the safe distance in overburden blasting activities at PT. Kuansing Inti Makmur, Bungo Regency, Jambi Province. This study uses a quantitative approach with field observation and regression analysis methods to evaluate the sensitivity of each parameter to the Flyrock distance that occurs by assessing the relationship between blasting geometry parameters, such as burden, spacing, stemming, blast hole depth, and powder factor, to the Flyrock throw distance. The analysis used a predictive model from Ebrahim Ghasemi (2012). The results of the study indicate that Flyrock is significantly influenced by the powder factor and other geometric variables, and indicate that the minimum safe distance for heavy equipment and humans is 300 meters and 500 meters, respectively, according to the provisions of the Minister of Energy and Mineral Resources Decree No. 1827 K / 30 / MEM / 2018. These findings are expected to be a reference in designing safer blasting in mining areas.